Luminescence and gain characteristics of 1.53 mu m broadband of Er3+ in lead telluroborate glasses - Kumar, M. V. Vijaya
Different concentrations (0.1, 0.5, 1.0 and 2.0 mol%) of Er3+-doped lead telluroborate glasses were prepared by conventional melt quenching method. Up on 514.5 nm laser excitation, the near infrared luminescence due to the I-4(13/2)-> I-4(15/2) transition was analyzed. The absorption and emission spectra were used to determine the different spectroscopic parameters by means of the Judd-Ofelt and the McCumber theories. The obtained Judd-Ofelt intensity parameters were used to obtain the radiative transition probability, fluorescence branching ratio and radiative lifetime of the I-4(13/2) emission state. The effect of Er3+ concentration on the emission intensity of I-4(13/2)-> I-4(15/2) transition was discussed. The Stark-level energies of I-4(13/2) excited and I-4(15/2) ground states were evaluated using both the absorption and emission measurements. The wavelength dependent gain coefficient, G(lambda) of I-4(13/2)-> I-4(15/2) transition of Er3+ ion was determined using the absorption and emission cross-sections. The suitability of this glass as a host for Er3+-doped broad-band amplifiers and its advantage over other glasses were discussed. (C) 2013 Elsevier B.V. All rights reserved.